Data for survival and growth of Scots pine (Pinus sylvestris) seedlings in north Sweden: effects of planting position and arginine-phosphate addition - Häggström, Bodil (Swedish University of Agricultural Sciences, 2021)
The purpose of the research study was to investigate the effects of and interaction between planting position, arginine-phosphate addition and location on survival and growth of Scots pine seedlings in north Sweden.

The study include 11 trial locations between latitudes 61.1 and 67.1 in the boreal forest of northern Sweden where forest had been harvested and mechanical soil preparation had been performed in 2017 either by mounding or disc-trenching. Scots pine seedlings were planted in May and June 2018. At each site seedlings were planted in three different planting positions, including seedlings treated with arginine-phosphate and untreated seedlings for each planting position. Survival- and growth inventory was performed in August and September 2019 following two growing seasons.

The data consists of survival and leader shoot length measurements of Scots pine (Pinus sylvestris) from inventory after two seasons in field at 11 sites across middle and north Sweden as well as site location coordinates, date of planting and inventory along with site environment variables.

The variables are described in detail in the documentation file. Data from SMHI has been used, see documentation file.

Two data files are included:
a. effects_position_APtreatment_data_leader_length.csv
b. effects_position_APtreatment_data_survival.csv

Field inventory was performed in the end of the second growing season during August-September 2019. All seedlings that had any green needles were registered as living, seedlings with no green needles and missing seedlings were registered as dead. Leader shoot length was measured from the base of the top branches to the top of the terminal bud. Every second alive and undamaged seedling was measured with random start at first or second seedling for each row. At sites where many seedlings were damaged or dead in any of the planting position-and treatment combinations, all remaining undamaged seedlings were measured from that combination.

Syftet med studien var att undersöka effekterna av och interaktionen mellan planteringspunkt, tillförsel av arginin-fosfat vid plantering och lokal på överlevnad och tillväxt av planterad tall i norra Sverige.

Studien inkluderar 11 lokaler mellan latituderna 61.1 och 67.1 i norra Sverige där skogen blivit skördad och markberedning utförts 2017. Tallplantorna planterades i maj–juni 2018. På varje lokal planterades plantorna i tre olika planteringspunkter med både tillförsel av arginin-fosfat och utan i varje planteringspunkt. Inventering av överlevnad och tillväxt utfördes hösten 2019.

Data består av registrerad överlevnad och tillväxt av årsskott från inventeringen 2019 från de 11 lokalerna samt koordinater, planteringsdatum, datum för inventering och lokalspecifika tillväxtmiljöbeskrivande variabler för varje lokal. Variablerna är beskrivna i detalj i dokumentationsfilen. Analysen har använt sig av SMHI-data, se dokumentationsfil.

Två datafiler är inkluderade:
a. effects_position_APtreatment_data_leader_length.csv
b. effects_position_APtreatment_data_survival.csv

Fältinventering utfördes i slutet av den andra tillväxtsäsongen i fält, under augusti och september 2019. Alla plantor som hade gröna barr registrerades som levande, plantor utan gröna barr och saknade plantor registrerades som döda. Längd på årsskotten på varannan levande oskadad planta mättes från de översta grenarnas bas till toppknoppen. På lokaler där många plantor var döda eller skadade i någon planteringspunkt mättes alla kvarvarande plantor i denna planteringspunkt.
Data för överlevnad och tillväxt av planterad tall (Pinus sylvestris) i norra Sverige: effekt av planteringspunkt och tillförsel av arginin-fosfat vid plantering
Keywords: planting position; planteringspunkt; arginine-phosphate; arginine-fosfat; Pinus sylvestris; Pinus sylvestris; Biological Sciences; Biologi; Ecology; Ekologi; Forest Science; Skogsvetenskap